Ethical, Legal, and Social Challenges in the Development and Implementation of Disaster Telemedicine. (4th October 2021) - Tedeschi, Christopher
ABSTRACT: In recent years, advances in communications technology and market factors have led to a substantial expansion of telemedicine practice. One potential use of telemedicine is in disaster response, both as a resource for responders as well as a direct link to patients. The advantages of using telehealth to assist in disaster response are accompanied by important questions related to social impact, ethical implications, and regulatory oversight. A narrative review of several of these issues is presented here. The next steps in the development of a robust disaster telemedicine system will include the development of best practices and ethical guidelines agreed upon by all stakeholders, as well as the development of public-private partnerships geared at providing the highest quality disaster telemedicine to the greatest possible number of patients.